Electrophoretically-deposited BiSbSe3 nanoparticles as highly efficient electrocatalysts for hydrogen evolution reaction. (June 2022) - Dileep, Naduvile Purayil; Puthenveettil, Lakshmi Kollenchery; Myakala, Stephen Nagaraju; Shaijumon, Manikoth M.
Highlights: BiSbSe3 nanoparticles are synthesized from exfoliated BiSbSe3 via electrophoretic deposition Electrocatalytic HER activity of BiSbSe3 nanoparticles is studied for the first time. We optimized the experiments and performed the catalytic measurements on BiSbSe3 . BiSbSe3 nanoparticles deposited at 7.5 V shows excellent HER activity in acidic medium. The obtained HER activity of BiSbSe3 nanoparticles is close to the Pt/C. Abstract: The development of highly effective, noble-metal-free electrocatalysts for hydrogen evolution reaction (HER) is vital for realizing future hydrogen energy systems. Antimony/bismuth-based chalcogenides are recently gaining wide attention as promising electrocatalysts for acidic HER due to their abundance, low cost, and tunable properties. Herein, we report a simple and unique approach for the synthesis of BiSbSe3 nanoparticles from exfoliated BiSbSe3 nanostructures through electrophoretic deposition. Bulk BiSbSe3 synthesized through a ball milling method is exfoliated through bipolar electrochemical route, and the process parameters are varied with respect to the time and applied voltage. From an aqueous solution of exfoliated BiSbSe3 nanostructures, we obtain BiSbSe3 nanoparticles directly deposited on to a gold substrate under varying applied voltages. Electrocatalytic activity of deposited BiSbSe3 nanoparticles is studied in 0.5 M aqueous H2 SO4 electrolyte using a 3-electrode set up. BiSbSe3 nanoparticles obtained through exfoliation process (10 V, 10 minutes), and deposited at 7.5 V (10V10M-Au-7.5) is identified as highly active electrocatalyst for HER, with a low onset potential of 37 mV, a low overpotential of 72 mV at a current density of 10 mA cm −2 and a low Tafel slope of 31.6 mV dec −1 in acidic medium, which is very close to the bench-mark Pt/C catalyst. Graphical abstract: Image, graphical abstract